2016
DOI: 10.1039/c6ra08683g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of various fluorescent protein–DNA binding peptides for effectively visualizing large DNA molecules

Abstract: Single-molecule DNA visualization with fluorescent protein DNA binding peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…This predicted value agrees relatively well with 14.03 μm (86%) observed for TAMRA-polypyrrole stained λ DNA in this report ( Supplementary Figure S3 ). In addition, this stretching result is consistent with stretching values (13.4–14.6 μm) for various fluorescent DNA binding proteins to stain DNA molecules in the same flow cell that we reported earlier ( 32 ). Therefore, 86% DNA stretch suggests that TAMRA-polypyrrole does not cause considerable structural deformation ( Supplementary Figure S3 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This predicted value agrees relatively well with 14.03 μm (86%) observed for TAMRA-polypyrrole stained λ DNA in this report ( Supplementary Figure S3 ). In addition, this stretching result is consistent with stretching values (13.4–14.6 μm) for various fluorescent DNA binding proteins to stain DNA molecules in the same flow cell that we reported earlier ( 32 ). Therefore, 86% DNA stretch suggests that TAMRA-polypyrrole does not cause considerable structural deformation ( Supplementary Figure S3 ).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, the DNA stretching rates indicated the degree of dye-induced structural deformation such as double helix unwinding. In our previous study, we reported that YOYO-1-stained DNA exhibited severe structural deformations resulting in 21.8 μm λ DNA in a flow cell, which corresponds to 134% stretching compared with native λ DNA (21.8/16.3 μm), but our previous computer simulation using finite element analysis predicted that native DNA should stretch 84% in the same flow cell ( 32 ). This predicted value agrees relatively well with 14.03 μm (86%) observed for TAMRA-polypyrrole stained λ DNA in this report ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 98%
“…First of all, TAMRA-polypyrrole stained DNA ( 2 in Figure 1) stretched up to 14.03 ± 0.54 µm ( X / L = 86% ± 3%) at 100 µL/min within 100 µm high flow cell [29]. Previously, we calculated the force of 0.79 pN applied to the λ DNA in the same flow cell (100 µL/min) [27]. Based on this value, we checked Bustamante’s paper, in which they measured DNA stretches versus the force by optical tweezers.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is notable that this stretch would be 88% ± 3% compared with Murade’s contour length (24.67 µm) for YOYO-1 stained DNA [28]. For comparison, we added DNA stretches stained by FP-DBPs (DNA binding peptides) from 6 to 10 in Figure 1 [21,27]. Figure 1 suggests that TAMRA-polypyrrole stained DNA preserves the contour length of natural B-form DNA, while YOYO-1 stained DNA changes it considerably.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation